Experimental investigation on an air source heat pump system with a novel anti-frosting evaporator. (25th February 2023) - Yu, Shipeng; Su, Yi; Cai, Weihua; Qiu, Guodong
Highlight: A novel reduced-frost evaporator for air-source heat pumps is proposed. Partial evaporator area remains frost-free under frosting conditions. The effective heating time of the air source heat pump was extended by 100–400 %. The COP is improved by 7%-17%. Abstract: The outdoor evaporator of the air source heat pump can easily be frosted during the winter heating operation, which significantly reduces the heating performance. Although anti-frosting and defrosting methods have been substantially researched, the challenges have not been well solved for a long time due to the inability to balance the cost, performance, and reliability. Therefore, to solve this problem, a new bowl shaped finned tube evaporator was proposed to restrain frosting by reducing the frosting driving force and increasing the frost growth resistance through the ingenious use of the fan vortex wind and gravity. A traditional evaporator that has the same finned tube type, total heat exchanger area, and fan power but a different shape structure to the proposed evaporator was selected as the comparison reference. Two experimental testing platforms were constructed to compare the performance characteristics between the proposed evaporator and the traditional one. Results indicated that the system with the proposed evaporator exhibited an increase of 7.4–17.3 % of the coefficient of performance, 100–400 % of the effective heating time, and 0.3–1.4 °C of indoor fan outlet temperature, as compared to the traditional evaporator. In addition, a frost-free area appeared in the proposed evaporator during the frosting period. Therefore, the proposed evaporator has a superior effect on space heating and energy conservation and it has good application in highly humid climates. Further research is recommended to increase the frost-free area and further improve the anti-frosting effect by optimizing the structure.